"Membingkai Melayu" Perancangan Metode Akting Berbasis Tradisi Untuk Pembelajaran Makyong di Program Studi Seni Pertunjukan UNIMED - Ilham Rifandi; Ikhsan Satria Irianto (SENDRATASIK UNP, 2023)
Theatrical discourse in Indonesia is still dominated by Western theater discourses, both theoretically and practically. This domination ordains theater as an art that is distant from the audience, including Makyong. As an effort to bring theater closer to the community, the development of acting methods based on ethnic traditions can be an alternative. The research method that will be used in this study is the Research and Development method developed by Thiagarajan, et al. The stages of implementing the research are as follows: Defining, Designing, Developing. The theory used as a basis in this study is the theory of postcolonial acting put forward by Asrul Sani and concept of theater anthropology from Eugenio Barba. The results of this study are Malay acting training methods arranged in the order of spiritual knowledge based on Tunjuk Ajar Melayu, pantun skills and body training based on Malay dance techniques. The development of the acting training method, which the author calls Framing Malay, aims to collect things that can help actors in creating Malay behavior.